JSE 30:4 Editorial - Braude, Stephen (Journal of Scientific Exploration, 2016)
Probably, most JSE readers already have at least a rough idea of what the term “synchronicity” means. The concept of synchronicity—it hardly deserves its familiar classification as a theory—is usually credited to Carl Jung (Jung 1973), although Jung really didn’t do much actually to clarify the notion. I’ll say something shortly about the problems with Jung’s approach, but what he had in mind—again, very roughly speaking—is this. We’ve all experienced coincidences in our lives: surprising combinations of events that appear to be causally unrelated. Of course, what surprises us about the events isn’t simply that they’re apparently unrelated causally. That’s true of many (if not most) pairs of events at any given time, and in fact the vast majority of events are completely unremarkable when considered in combination. The event-clusters in a coincidence attract our attention first, because something about their combination seems personally noteworthy or strange, and second because we consider that combination to be more or less improbable. In fact, the more improbable we believe the event-clusters to be, the more significant and remarkable the coincidences are likely to seem.